All against Hollywood: Policies in defence of national cinematography in European countries after World War I - Daniela Manetti (The Journal of European Economic History (JEEH), 2023)
During the First World War, the film industry of the major European countries experienced a lasting crisis, which necessitated significant restructuring and prompted appeals for state intervention to counterbalance the invasion of American films. As the extent of this crisis did not affect all nations equally, each pursued its own course in the attempt to defend its products and markets from the competition and success of Hollywood films (through measures such as tariffs, quota systems and importation prohibitions). This essay aims to present a comparative analysis of these policies.
Keywords: 330; Film industry; Industry development; Film policy war; Post-war period; USA; France; Great Britain; Europe; Filmwirtschaft; Branchenentwicklung; Filmpolitik; Weltkrieg; Nachkriegszeit; USA; Frankreich; Großbritannien; Europa